POLA INVESTASI TENAGA KERJA WANITA INDONESIA DI DESA SIKANCO KECAMATAN NUSAWUNGU KABUPATEN CILACAP - Ma’sumah, Siti (El-Jizya : Jurnal Ekonomi Islam, 2019)
Islam teaches that husbands are obliged to provide for their families. But not a few women are just working after they get married to help the family's economy. Family background that is not capable of causing people not to have higher education. Low education makes people work in the informal sector with relatively low salaries. The low salary received is not enough to meet daily needs, especially the needs of clothing and shelter. This shortage triggered the wives to work abroad with high salaries even though they worked in the informal sector. This study aims to describe the investment pattern of Indonesian female workers in Sikanco Village, Nusawungu, Cilacap District. The results of this study concluded that the informants who invest in savings are many but over time their savings are used up to meet their daily needs. The majority of female workers do not invest in deposits, only one person has ever invested in deposits. However, as time went on after returning to Indonesia, the deposit was used up because migrant workers did not have income, so they used the deposit money to sufficient needs. There are no migrant workers who invest in shares. This is because of the ignorance of the migrant workers and their families about investing in shares. The majority of informants invest in property because it is in the investment village because more investment villages are chosen. Investment in collectibles such as motorbikes and cars is quite attractive to informants because it can be used as a means of transportation. The majority of respondents invest in gold, because in addition to investing in gold can be used as jewelry. Many female workers who were respondents in this study kept foreign currency, but it ran out over time. There are no respondents who invest in bonds, because of the unknown knowledge of migrant workers and their families regarding bonds.